A multi-scale analysis of habitat selection in peripheral populations of the endangered Dupont's Lark Chersophilus duponti. Issue 3 (17th October 2016) - PÉREZ-GRANADOS, CRISTIAN; LÓPEZ-IBORRA, GERMÁN M.; SEOANE, JAVIER
Summary: Habitat selection of endangered species in peripheral populations must be considered when designing effective conservation plans, as these populations tend to occupy atypical habitats where species-environment relationships are not well understood. We examined patterns of habitat use in peripheral populations of the endangered Dupont's Lark Chersophilus duplonti using a multi-scale approach and assessed the spatiotemporal transferability of these models to test for their generality. Our results show that at microhabitat (circles of 50-m diameter used by the species versus random points) and macrohabitat (occupied/unoccupied squares of 1 ha) scales the species selected flat and non-forested areas, but at the microhabitat scale the cover of small shrubs was also important. Models developed at patch scale (occupied /unoccupied sites) identified only site size as an important predictor of species occurrence. Habitat models transferred successfully among sites and years, which suggests that these models and our recommendations may be extrapolated over a larger geographic area. A multi-scale approach was used for identifying conservation requirements at different spatial scales. At the patch scale our models confirm it is a priority to maintain or enlarge the extent of habitat patches to ensure the viability of the studied metapopulation. At the macrohabitat scale our results suggest that reducing tree density in low slope areas would be the most effective management action. At the microhabitat scale, encouraging the presence of small and medium-sized shrubs, by clearing certain scrubs (e.g. large brooms Genista spp. and rosemary Rosmarinus officinalis ) or promoting traditional low-level extensive grazing, should increase the availability of high-quality habitats for the species, and thus the number of potential territories within a patch. These recommendations largely coincide with the ones given for core populations at specific scales elsewhere.